When Walking Fails : Mobility Problems of Adults with Chronic Conditions - Iezzoni, Lisa I. (Book collections on Project MUSE., 2003)
Roughly one in ten adult Americans find their walking slowed by progressive chronic conditions like arthritis, back problems, heart and lung diseases, and diabetes. In this passionate and deeply informed book, Lisa I. Iezzoni describes the personal experiences of and societal responses to adults whose mobility makes it difficult for them to live as they wish--partly because of physical and emotional conditions and partly because of persisting societal and environmental barriers.